20.8k views
5 votes
Solve for x -48=6(x-3)

2 Answers

4 votes

Answer:

x = - 6

Explanation:

x - 48 = 6(x - 3)

Expand the terms in the bracket

That's

x - 48 = 6x - 18

Group the constants at the right side of the equation and the ones with variables at the left side

x - 6x = 48 - 18

- 5x = 30

Divide both sides by - 5

x = - 6

Hope this helps you

User Tddmonkey
by
4.9k points
7 votes

Answer:


\boxed{x = -6}

Explanation:


x-48 = 6(x-3)

Resolving parenthesis


x - 48 = 6x-18

Adding 18 to both sides


x-48+18 = 6x\\x-30 = 6x

Subtracting x from both sides


-30 = 6x-x\\-30 = 5x

Dividing both sides by 5


-30/5 = x


-6 = x\\

OR

x = -6

User Istari
by
4.4k points